Apoio institucional como determinante para ecoeficiência nas micro e pequenas empresas industriais: um estudo de caso para o município de Maceió - Melo, Luzia Maria Cavalcante de (2006)
The objective of this study is to check the existent articulation between the institutional arrangement favorable to the echo-efficiency and the industrial MSCs (Micro and Small Companies) in the city of Maceió as a determinant to the use of echo-efficiency measures by these companies. The choice of the municipal district of Maceió as a case study is due to the importance of MSCs in the economy of Alagoas, which represents 98, 7% of the total existing companies in this state, where 54% of them are concentrated in Maceió. This research takes the hypothesis that the limitation of resources and knowledge in relation to environmentally correct manners of production are factors that hinder the echo-efficiency adoption in those companies. For this reason, the institutional support is fundamental so that industrial MSCs in Maceió adopt echo-efficiency measures. For that, a mapping of the main institutions was made with its actions related to the environmental subjects close to MSCs. It was verified that the institutional support is of fundamental importance to the MSCs echo-efficiency. Therefore, the institutional apparatus that works the echo-efficiency in those companies is insignificant.